(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the importance of SMART technology in the cultivation of agricultural crops in the greenhouse. SMART’s methodology shows opportunities to improve productivity in agriculture based on clear goal setting, measurable outcomes, and achievable goals, meaningful and time-dependent goals. Greenhouses provide innovative approaches to managing climatic conditions, saving resources, pest control and improving quality. The article highlights the need for Sustainable Development and environmental security through technological innovations in agriculture and their implementation.